Accuracy and perceptions of teledentistry in KSA during the COVID-19 pandemic: A single-centre randomised controlled trial. Issue 3 (June 2022) - Aboalshamat, Khalid T.; Althagafi, Tariq K.; Alsaeedi, Saad A.; Alhumaidi, Saif N.; Alemam, Amjad A.
الملخص: أهداف البحث: يقدم طب الأسنان الاتصالي رعاية صحية للأسنان عند تعذر زيارة عيادة الأسنان مثل أوقات جائحة كوفيد-١٩. هدف هذه الدراسة هو تقييم دقة طب الأسنان الاتصالي في تشخيص حالة المرضى مقارنة بتشخيص زيارة عيادة الأسنان التقليدية وتقييم الانطباعات والمعرفة والسلوك والتحديات لدى مرضى الأسنان عن طب الأسنان الاتصالي، خلال جائحة كوفيد-١٩ في المملكة العربية السعودية. طرق البحث: تم استخدام دراسة عشوائية محكمة متوازية ومعمية لجهة واحدة. تم توزيع 70 مشارك بشكل عشوائي إلى مجموعتين: مجموعة التجربة ومجموعة ضابطة. خضعت مجموعة التجربة إلى التشخيص عن طريق طب الأسنان الاتصالي، في حين كانت المجموعة الضابطة في فترة الانتظار. تم مقارنة نتائج تشخيص مجموعة التجربة بنتائج تشخيصهم السريرية الأولية في ملفات مستشفى الأسنان. بعد انتهاء التجربة أجاب جميع المشاركين من المجموعتين على أسئلة استبانة الدراسة. النتائج: لا توجد فروق ذات دلالة إحصائية بين المجموعتين في المعرفة والسلوك تجاه طب الأسنان الاتصالي، ولكن حصلت مجموعة التجربة على تجربة إيجابية أعلى مقارنة بالمجموعة الضابطة. بلغت دقة تشخيص مجموعة التجربة باستخدام طب الأسنان الاتصال مقارنة بنتائج التشخيص السريري الأولي على النحو التالي: 74.3% بالنسبة للشكوى الأساسية، و74.3% بالنسبة لعدد الأسنان المفقودة، و 71.4% للأسنان المعالجة بالحشوات، و 65.7% لحالة نظافة الفم. بلغت دقة التشخيص 51.4% للمشاكل الصحية، و 40% بالنسبة لتشخيص تسوس الأسنان. عند استخدام طب الأسنان الاتصالي تم تشخيص عدد أكبر في الأسنان المصابة بالتسوس، وعدد أكبر في مؤشر الأسنان المتحللة والمفقودة والممتلئة بفارق ذو دلالة إحصائية، عند مقارنتها بنتائج التشخيص السريري الأولي. الاستنتاجات: يحظى طب الأسنان الاتصالي بقبول واسع بين مرضى الأسنان ويمكن أن يستعمل بشكل فعال لفحص الأسنان بشكل مبدئي، خصوصا خلال فترات الحجر الصحي خلال الأوبئة، لكن يجب أن يتبعه فحص سريري في العيادة للحصول على تشخيص اكثر دقة. Abstract: Objective: Teledentistry conveniently delivers dental care when in-person visits are restricted, such as during the COVID-19 pandemic. This study aimed to assess Saudi Arabian patients' accuracy, perceptions, knowledge, attitudes, and challenges regarding teledentistry used for diagnosis during the COVID-19 pandemic, as well as its accuracy, versus traditional dental visits. Methods: A single-blind, parallel-group randomised controlled trial design was used. The 70 participants were randomised equally into study and control groups. While the control group waited, the study group received teledentistry diagnoses which were compared with baseline clinical examinations retrieved from the UQU dental hospital, Makkah, KSA. After the intervention was completed, all participants answered a questionnaire. Results: There were no significant differences between the groups in knowledge or attitudes regarding teledentistry. However, study group participants had more favourable experiences with teledentistry. They reported good accuracy with diagnosis and recording of their chief complaints (74.3%), number of missing teeth (74.3%), number of filled teeth (71.4%), and oral hygiene status (65.7%). Additionally, moderate accuracy was reported on recording of health complaints (51.4%) and number of decayed teeth (40.?%). The number of decayed teeth and the decayed, missing, and filled teeth (DMF) index scores reported using teledentistry were significantly ( p  < 0.05) higher than reported in the baseline examinations. Conclusion: Teledentistry is widely accepted by patients and can be efficient for preliminary examinations, particularly during pandemic lockdowns or in more frequently occurring situations such as severe weather conditions, but subsequent clinical examination is necessary for maximally accurate diagnoses.